Diabetes on demand and novel technologies. Issue 2 (15th February 2018) - Maurizi, A.R.; Piemonte, V.; Pozzilli, P.
Abstract: To date, the use of technology for the management of diabetes represents a promising area of innovation that can dramatically change diabetics' lives. In the past decade, the use of diabetes devices has widely grown and looks to have partially improved diabetes management. The combination of cloud technology with real‐expert intervention saves time and improves efficiency, as well as empowering the patient. The application of mathematical models applied to diabetes therapy could lead to significant improvement in life quality and challenge the burden of hypoglycaemia. Events where an individual needs support are instantly achieved, triggering outreach alerts via cloud and wireless connectivity, thereby improving patient compliance and reducing disease costs.